Sediment loss patterns in the sub-humid Ethiopian Highlands - Dagnew, D.C.; Guzmán, Christian D.; Zegeye, Assefa D.; Akal, Adugnaw T.; Moges, M.A.; Tebebu, T.Y.; Mekuria, Wolde; Ayana, Essayas K.; Tilahun, Seifu A.; Steenhuis, Tammo S. (Wiley, 2017)
Controlling soil erosion is important for maintaining land productivity and reducing sedimentation of reservoirs in the Ethiopian highlands. To gain insights on sediment loss patterns, magnitude of peak sediment events, and their contribution to annual loads, hydrometric and sediment concentration data were collected for five years (2010 – 2014) from the 95 ha Debre Mawi and four nested catchments (located 30 km south of Lake Tana). Soil and water conservation practices (SWCPs) consisting of soil bunds with 50 cm deep furrows were implemented in the third year, which made it possible to examine the effects of SWCPs on peak sediment loads. The results show that a 10-minute event causes soil loss of up to 11.4 Mg ha-1, which is 22% of the annual sediment yield. Thirty to seventy-five percent (up to 30 Mg ha-1day-1) of the sediment yield was contributed by the greatest daily flow in each year. The contribution increases to 86% for the two largest daily flows. SWCP interventions reduced sediment loss by half but did not affect the relative contribution of peak events to annual loads. Due to gully erosion, peak sediment loads at the outlet of the entire catchment were greater (up to 30 Mg ha-1day-1) as compared to the nested catchments without gullies (0.5 to 8 Mg ha-1day-1). Consequently, to reduce sediment loss, conservation measures should be designed to decrease runoff during large storms. This can be attained by deepening furrows on unsaturated hillsides and reducing the entrainment of unconsolidated sediment from failed gully banks.